THE MEDICINAL PROPERTIES OF LEMON AND THE ROLE OF HUMAN HEALTH (Multidisciplinary Journal of Science and Technology, 2024)
Today, folk medicine is very rich and enriched with great experience and knowledge. It is an inexhaustible source that enriches scientific (official) medicine with new, effective medicinal preparations. The value and role of folk medicine in this field is incomparable. At the same time, it should be noted that most of the medicinal plants used in modern medicine are taken from the treasure of folk medicine, or that scientific medicine itself is developing on the basis of folk medicine, that most of the medicinal plants used in folk medicine are taken from the treasure of folk medicine. it should be noted. health and prevention of many diseases. it should be noted that it is working.